2000
DOI: 10.1063/1.1320856
|View full text |Cite
|
Sign up to set email alerts
|

The semiclassical propagator for spin coherent states

Abstract: We use a continuous-time path integral to obtain the semiclassical propagator for minimal-spread spin coherent states. We pay particular attention to the "extra phase" discovered by Solari and Kochetov, and show that this correction is related to an anomaly in the fluctuation determinant. We show that, once this extra factor is included, the semiclassical propagator has the correct short time behaviour to O(T 2 ), and demonstrate its consistency under dissection of the path.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
133
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(135 citation statements)
references
References 39 publications
(54 reference statements)
0
133
0
2
Order By: Relevance
“…The quantities T r and T c = τ c / ν are usually called revival time and classical time [33]. Let us turn to the semiclassical approximation, which has been analyzed in some previous works [5,10,11]. The classical Hamiltonian is…”
Section: The Semiclassical Propagatormentioning
confidence: 99%
See 3 more Smart Citations
“…The quantities T r and T c = τ c / ν are usually called revival time and classical time [33]. Let us turn to the semiclassical approximation, which has been analyzed in some previous works [5,10,11]. The classical Hamiltonian is…”
Section: The Semiclassical Propagatormentioning
confidence: 99%
“…It has been shown that, in the semiclassical limit j → ∞, = 1/j → 0, this can be approximated by [10,11] …”
Section: The Semiclassical Propagatormentioning
confidence: 99%
See 2 more Smart Citations
“…Yet another detailed derivation has also been presented by Stone et al [24], focusing on the importance of the extra term (see also Ref. [25]), which has received the name of SolariKochetov phase.…”
Section: Introductionmentioning
confidence: 99%